Secure access authentication scheme for 4G wireless network based on PCL - Li-li WANG; Tao FENG; Jian-feng MA (Tongxin xuebao)
Considering the access authentication for mobile terminals in the 4G wireless network,a new secure access authentication scheme based on the self-certified public key system was designed.Then the deductive process of the scheme was derived with the protocol derivation system and its security attributes was formally proofed with protocol composition logic.By the security proof and comprehensive analysis,it is showed that the proposed scheme not only has session authentication and key confidentiality,but also can defend pseudo-base station attack and reply attack,provide the undeniable service and identity privacy.Moreover,the scheme can improve the access efficiency of the mobile terminals.